THE MEDICAL AND SOCIAL PROBLEM OF RECURRENT AND CONTACT CARIES - Ольга Сергеевна Пухова; Владмир Маркович Корчемный; Ксения Сергеевна Киселева; Сергей Владимирович Черненко; Ольга Сергеевна Корчемная; Елена Александровна Киселева; Елена Александровна Тё; Динар Минзагитович Гарафутдинов; Маргарита Владимировна Сергеева; Игорь Анатольевич Тё; Светлана Ивановна Елгина; Елена Владимировна Рудаева; et al. (Медицина в Кузбассе, 2023)
Caries is the most common cause of damage to the hard tissues of the teeth. Among the Russian population, the prevalence and intensity of caries reaches 99 %, the percentage of its complications remains high and reaches 30-32 %, requiring repeated therapy for recurrent caries. The resistance of the hard tissues of teeth to caries is affected by structural disorders in hypoplasia and other diseases of the teeth of non-carious origin, but a number of issues regarding the etiology and pathogenesis of dental caries remains controversial and is subject to further study.